Incorporation of health technologies: The importance of drug treatment of primary headaches in the Brazilian unified health system - Godoi, André Luiz; Santos, Erlene Roberta Ribeiro dos; Andrade, Juliana Ramos (Headache Medicine, 2022)
Incorporation of health technologies: The importance of drug treatment of primary headaches in the Brazilian unified health system